THE VALIDITY OF STUDENT WORK SHEETS BASED ON CONTEXTUAL TEACHING AND LEARNING (CTL) IN ENVIRONMENTAL CHANGE MATERIAL TO TRAIN SCIENTIFIC LITERACY SKILLS - Dewi, Paramastri; Indana, Sifak (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2019)
Abstract Scientific literacy is the ability to use scientific knowledge in increasing understanding and applying knowledge to daily life. Contextual Teaching and Learning is an approach Â that connects learning materials to real conditions, hence student can apply their knowledge. This study aimed to describe the validity of student worksheets based on Contectual Teaching and Learning on Environmental Change material to train the scientific literacy skills. Development of Student Worksheets based on Contextual Teaching And Learning was conducted in the Biology Department of the Mathematics and Science Faculty, State University of Surabaya. This study was a developmental research that used 4-D model consisted four stages namely define, design, develop, and disseminate. The result of the validity was obtained based on the assessment scores of an education expert, a material expert and a Biology teacher. Validation criteria of student worksheets included the appropriateness of the content, presentation, language, suitability of the principles of the CTL stage, and scientific literacy skills. The result was analyzed descriptive quantitatively. The research result showed that the student worksheet obtained an averange score of 3.91 including very valid categories. Keywords: Student Worksheets, Contextual Teaching and Learning, Scientific Literacy Skills, Environmental Change material.